Fisheries and Aquaculture in the Modern World - Mikkola, Heimo (IntechOpen, 2016)
This book has nine chapters on Aquaculture Wetland Ecosystem Services Approach and Climate Change Adaptation, which explain how different aquaculture systems could maximize the benefits that society receives from both aquaculture production and the ecosystem services provided by wetland ecosystems. Sustainable development of aquaculture must take into account the societal value of ecosystem services for an efficient and environmentally sound production of food. Although some issues regarding the potential benefits and implementation of sustainable aquaculture remain, the consideration of food security and minimizing ecosystem impacts suggest that the time has come to take action. If we can efficiently farm the land, why can't we farm more the sea and inland waters?